Exploring The Way The Lecturer Develop Reading Material at State Islamic Institute of Lhokseumawe - Cut Barlianti Taufiqiani; Teuku Zulfikar; Usman Kasim (English Education Journal, 2019)
Reading material is one of the required subject stated in the curriculum at English Department of State Islamic Institute of  Lhokseumawe which is designed by the lecturer for her own class. In order to create high quality material, the lecturer has to consider the procedure of reading material development according the theory that stated by expert. The research objective of this study were the types of reading text used by the lecturer in teaching, and to describe the process of reading materials development the lecturer did. The research subject was the lecturer who teach Reading Comprehension III at English Department of State Islamic Institute of  Lhokseumawe. The data of this research were collected by using two research instruments, there were interview guide and documentation. In order to collect the data, the lecturer was given the questions of interview. Furthermore, in order to find out the type of reading text used by the lecturer, the researcher used the documentation. Finally, all the data were analyzed by using procedure of data analysis in qualitative methodology, there were three steps; first, organization and familiarization; second, coding and reducing process, and the last was interpreting and representing. From the data analysis result, it is found that first, the lecturer used one descriptive text for the first material and the rest belongs to expository text; and Second, the lecturer used five of seven steps of Tomlinson model in developing material process there were; First, identification stage to identify the needs of the students; Second, exploration of the need; Third, contextual realization stage; Fourth, pedagogical realization stage; Fifth, production of materials.